Journey into the Unknown? Economic Consequences of Factor Market Integration under Increasing Returns to Scale - Thomas Steger; Andreas Schäfer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
What are the dynamic consequences of comprehensive integration shocks? The answer to this question appears all but trivial. We set up a dynamic macroeconomic model of a small open economy where both capital and labor are mobile and there are increasing returns to scale at the aggregate level. The model features multiple equilibria as well as (local and global) indeterminacy. Hence, expectations matter for resulting equilibrium dynamics. Despite its simplicity, the model creates a rich set of plausible implications. Our analysis contributes to a better understanding of the interaction between expectations and fundamentals in models with indeterminacy. The model is applied to replicate two striking empirical characteristics of macroeconomic development in East Germany since 1991.
Keywords: D90; F20; O10; 330